2016
DOI: 10.1186/s12891-016-0932-z
|View full text |Cite|
|
Sign up to set email alerts
|

Hidden musculoskeletal involvement in inflammatory bowel disease: a multicenter ultrasound study

Abstract: BackgroundInflammatory bowel diseases are associated with a variety of extra-intestinal manifestations. The most frequent of these is joint involvement, which affects 16–33 % of IBD patients. Our aim was to evaluate the ultrasound prevalence of sub-clinical joint and entheseal involvement in patients with IBD without musculoskeletal symptoms, and to correlate the US findings with clinical and laboratory variables.MethodsWe recorded the clinical and laboratory data of 76 patients with IBD, 20 patients with spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…On the other hand, the association between our US findings and the clinical questionnaire responses was weak or nonexistent. In other studies of musculoskeletal US performed in subjects with IBD, a high prevalence of subclinical US abnormalities has been found [ 17 , 18 ]. Something similar has been published in patients with psoriasis without arthritis [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the association between our US findings and the clinical questionnaire responses was weak or nonexistent. In other studies of musculoskeletal US performed in subjects with IBD, a high prevalence of subclinical US abnormalities has been found [ 17 , 18 ]. Something similar has been published in patients with psoriasis without arthritis [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…This was similar to adult IBD studies in which both physical and US examinations had been performed and the frequencies had been reported to be between 44.3-84.1%. 34,35 In a meta-analysis performed for the prevalence of the axial and peripheral manifestation in adults with CD and UC, the prevalence of the peripheral manifestations such as enthesitis was reported to range between 1-54%. 36 Jousse-Joulin et al 5 found that entheseal tenderness does not always correspond to ultrasound abnormalities while radiographic enthesitis is also not associated with positive physical examination findings, suggesting subclinical enthesitis.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian cross-sectional study involving 81 IBD patients without musculoskeletal symptoms revealed gray-scale lower limb entheseal alterations in 71 (92.6%) cases and a positive power Doppler in 13 (16%) [43]. A multicenter cross-sectional study of IBDs 76 patients highlighted that 64 (84.1%) had at least one grayscale entheseal alteration, 11 (13.9%) one entheseal positive power Doppler, and 32 (42.1%) sub-clinical joint involvement [44]. A Turkish monocentric cross-sectional study including 43 IBDs, 44 celiac patients and 18 healthy controls found higher entheseal gray-scale and power Doppler US alterations in the two pathological groups [45].…”
Section: Imaging In the Assessment Of Non-inflammatory Musculoskeletamentioning
confidence: 99%